Profile of injury acute renal in candidates to heart transplantation in a reference hospital - Magalhães, Nasser Câmara; Fernandes, Lenise Castelo Branco Camurça; Fernandes, Paula Frassinetti Castelo Branco Camurça; Oliveira, Ítalo Martins De; Figueiredo, Joana Tássia Pinheiro De; Souza Neto, João David De; Bacal, Fernando; Figueiredo, Joana Thayne Pinheiro de; Queiroz, Gabriel Moreira Furtado de (Brazilian Journal of Transplantation, 2014)
Introduction: Acute kidney injury (AKI) is a loss of sudden and potentially fatal kidney function. It has a high prevalence in patients with heart failure (HF), and may also limit the effectiveness of treatment, increasing morbidity and mortality. Objectives: To analyze the clinical and epidemiological profile of acute kidney injury in a sample of patients eligible for cardiac transplantation in Cear . Methods: Cross-sectional descriptive study conducted at Hospital Dr. Carlos Alberto Gomes Studart, between December 2011 and April 2013, evaluating LRA in 24 patients awaiting heart transplantation, using the Acute Kidney Injury Network (AKIN) criteria. Results: The prevalence of acute kidney injury in this series was 25%, four in stage I, one in stage II and stage III of the AKIN. Discussion: The association of renal injury with heart failure is due to a complex cardiorenal interaction called cardiorenal syndrome. The staging of chronic kidney disease, patients with glomerular filtration rate GFR <60 ml / min / 1.73m2 have a higher risk of mortality. The LRA also is bad prognostic marker, the application requiring the AKIN criteria for early diagnosis. Conclusion: Due to high morbidity and mortality of acute kidney injury in this group of patients with severe heart failure and potentially unstable, early diagnosis and appropriate treatment is essential for better prognosis.